1996
DOI: 10.1002/(sici)1096-9861(19960122)364:4<677::aid-cne6>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and postmetamorphic organization of the vestibular nuclear complex in the turbot examined by retrograde tracer substances

Abstract: During metamorphosis of flatfish larvae, eye migration leads to a 90 degrees misalignment of the visual and vestibular frames of reference. In order to maintain vestibular eye stabilization, the vestibulo-ocular (V-O) pathways have to be radically reorganized. Here, we have examined the vestibular projections in turbot larvae and juveniles by means of conventional neurohistological techniques using horseradish peroxidase and fluorescent dextranamines as tracers. We have found that the vestibular projections to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…The variable bilaterality of the adult connections could then be a later addition to a stereotyped, completely lateralized scaffold of projections. Interestingly, it has been reported that there is a large increase in bilaterality of the vestibulo-ocular projection between larval and juvenile turbot [31]. This increase has been correlated to eye migration during metamorphosis of the flatfish [31], but our observations of the early zebrafish brain suggest that increased bilaterality may be a general feature of post-embryonic development.…”
Section: Discussionmentioning
confidence: 61%
“…The variable bilaterality of the adult connections could then be a later addition to a stereotyped, completely lateralized scaffold of projections. Interestingly, it has been reported that there is a large increase in bilaterality of the vestibulo-ocular projection between larval and juvenile turbot [31]. This increase has been correlated to eye migration during metamorphosis of the flatfish [31], but our observations of the early zebrafish brain suggest that increased bilaterality may be a general feature of post-embryonic development.…”
Section: Discussionmentioning
confidence: 61%
“…However, the gross anatomy and bilateral symmetry of the labyrinths in flatfish (Jacob, 1928), the distribution of the vestibular nuclear complex in the hindbrain of larval and juvenile turbot Scopthalmus maximus (Jansen and Enger, 1996), and the peripheral and central oculomotor apparatus (Graf and Baker, 1985) are bilaterally symmetrical and similar to those of other teleosts. Interestingly, all flatfish except for the most primitive (Platt, 1983) display nearly omni-directional hair-cell polarization of the inner ear's saccular and lagenar otoliths (Jorgensen, 1976;Platt, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Соответствующая мигрирующему глазу вестибулярная система (отолит и лабиринт) не смещаются, однако, во время изменений, связанных с метаморфозом, происходит существенное увеличение числа нейронов, ведущих от глазного нерва к вестибулярно-нервному комплексу головного мозга, и происходит их реогранизация (Jansen, Enger, 1996). Несмотря на то, что отолиты остаются на обеих сторонах головы, реорганизация нейронов означает, что у рыб изменяется невральное определение физического значения «верх».…”
Section: феномен метаморфоза камбалообразныхunclassified